2021
DOI: 10.3390/pr9081408
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Fluctuation Reduction of a Centrifugal Pump by Blade Trailing Edge Modification

Abstract: The pressure fluctuation inside centrifugal pumps is one of the main causes of hydro-induced vibration, especially at the blade-passing frequency and its harmonics. This paper investigates the feature of blade-passing frequency excitation in a low-specific-speed centrifugal pump in the perspective of local Euler head distribution based on CFD analysis. Meanwhile, the relation between local Euler head distribution and pressure fluctuation amplitude is observed and used to explain the mechanism of intensive pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The mainstream approach to blade edge modifications involves employing similar offset and cutting operations from the shroud to the hub [2][3][4][5][6][7]. Some scholars have also modified the trailing edge unilaterally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mainstream approach to blade edge modifications involves employing similar offset and cutting operations from the shroud to the hub [2][3][4][5][6][7]. Some scholars have also modified the trailing edge unilaterally.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [2] conducted cutting operations on the pressure side of the blade trailing edge, effectively improving the uniformity of the blade exit. Similarly, Huang et al [3] implemented unilateral pressure-side cutting to reduce the exit angle of the impeller's pressure surface, thereby adjusting the velocity component at the impeller exit and influencing the pressure pulsations within the pump. Some researchers have attempted to simultaneously modify both the pressure and suction sides.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that EPS (ellipse on pressure side) and EBS (ellipse on both sides) can both reduce the eddy current intensity at the trailing edge of the blade, significantly improve the efficiency of the pump, and reduce the pressure pulsation. Huang et al [25] found that filing the trailing edge of the blade reduces the outlet angle of the blade, leading to an increase in head and a decrease in pressure pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Periodic pressure fluctuations may force the impeller to vibrate, and resonance may occur when the frequency of pressure fluctuation approaches the natural frequency of pump components. 5 On the other side, unbalanced axial and radial force generate higher vibration amplitudes which affect the life cycle of the pump's shaft and bearing. The generation of these pressure fluctuations and unsteady axial and radial forces consequently affect the mechanical integrity of the pump.…”
Section: Introductionmentioning
confidence: 99%